Optimization of Nitrogen Fertilization and Seedling Density of A New Rice Type (Oryza sativa L.) “IPB 3S” - Sugiyanta, Sugiyanta; Kusuma, Galih Angga (Journal of Tropical Crop Science, 2017)
The new plant type of rice, or ‘padi tipe baru’ (PTB) in Indonesian, is a new group of rice cultivars with a higher productivity compared to the modern rice varieties (‘varietas unggul baru’ or VUB). This study was conducted to determine the optimum dose of nitrogen fertilization and the seedling density or number of seedlings per hill to increase growth and yield of the new type of rice “IPB 3”. The experiment was conducted in the Bogor Experimental Station  in January to June 2015.  Nitrogen doses (90, 120, 150, 180 kg N.ha-1) and number of seeds per hill (1, 5, 10, 15 and 20) were tested.  The results showed that the increased dose of nitrogen fertilizer reduced the percentage of filled grains, the rate of photosynthesis and the grain yield per hectare. Similarly, an increase in the seedling density up to 15 seeds decreased the dry matter of the crop, the number of grains per panicle, and grain weight per plant, but increased the grain yield per hectare. The optimum yield of “IPB 3S” was achieved with  90 kg N.ha-1 with 15 seeds per hill. The results of this study have provided a guideline for an improved nitrogen management in relation to rice seedling population to increase yield of a new rice type “IPB3S”.Keywords:  “IPB 3S”, new plant type, fertilizer, local variety